Say yes to your potential / by Skip Ross with Carole C. Carlson - "Ross, Skip" (Bhopal, 2011)
Teaches how to tap the 90 percent might-have-been potential and turn it into an exciting and dynamic quality of life. Offers solid practical advise, gleaned from real-life experiences.
Keywords: Personal development